Artificial Competition - A legal analysis of Article 6(5) DMA and potential self-preferencing concerns arising from Google’s AI Overviews - Utterström,Patrik (2025)
In 2022, the Digital Markets Act (DMA) entered into force as a regulation adopted by the European Union with the objective of safeguarding contestability and fairness in digital markets, in particular by addressing the conduct of very large undertakings that are able to leverage their economic position to the detriment of competitors. Such undertakings are designated as “gatekeepers” under the DMA and are characterized by their capacity to control access points, or “gateways”, between business users and end users in digital markets. In effect, the Regulation imposes obligations on designated gatekeepers without requiring the Commission to demonstrate a risk of negative market effects or to engage in an effects-based assessment of efficiency or contestability. A core provision of the DMA is Article 6(5), which prohibits gatekeepers from utilizing their core platform services e.g. search engines, operative systems or intermediation services, to promote other businesses provided by the same economic beneficiary. The provision is comparable to the case law regarding Google Shopping, in which Google leveraged its search engine to favor its own comparison-shopping service over competing services, a practice that resulted in the imposition of a fine by the European Commission. In March 2025, Google launched AI Overviews in the European Union. The tool is designed to generate synthesized responses by compiling information from multiple sources using artificial intelligence. When activated, AI Over-views are displayed in a prominent position on Google Search’s search engine results page, thus, demoting other websites that are often dependent on clicks to generate ad-revenue. This practice raises the question of whether such placement may fall within the scope of the prohibition on self-preferencing laid down in Article 6(5) of the DMA, an issue which this thesis seeks to assess. First, the provision of self-preference is described as well as how it has been implemented thus far in case law and practice by the EU Commission. The second part is an evaluation of the provision’s requirements for applicability in relation to AI Overviews. The last part of this essay analyses whether Google is engaging in self-preference because of how AI Overviews are used today. It also includes a discussion of the DMAs overall objective and if its effective enough to counter potential market concerns regarding the integration of AI into other ser-vices provided by Gatekeepers.
Keywords: EU law; competition law; Digital Markets Act; Self-preference